Impacts of Ambrosia trifida Invasi on plant biodiversity - Yin Pingping, Shenyang agricultural university, Shenyang (China), College of Agronomy; Li Jiandong, Shenyang agricultural university, Shenyang (China), College of Agronomy; Yin Hong, Shenyang agricultural university, Shenyang (China), College of Agronomy (Xi bei nong lin ke ji da xue xue bao.Zi ran ke xue ban, 2010)
了解三裂叶豚草的生长群落，分析三裂叶豚草入侵对生物多样性的影响。于2008-05-28―06-28，利用样方法，调查沈阳东陵公园附近公园（5个样点）、农田（3个样点）、高速公路附近（4个样点）、桑园（4个样点）和路边（4个样点）5个生境中，三裂叶豚草分布样点杂草的种类和分布情况。所调查生境分布样点中，共有杂草28科71种，其中以菊科、藜科、蓼科居多。从发生频率10%的34种杂草在前2个主成分上的负荷量可以看出，影响三裂叶豚草的主成分因素是人为干扰程度和土壤水分条件，可知三裂叶豚草是喜干扰且适宜生活在土壤水分含量较大的生境内，据此将分布样点分为3个聚类群。随着人为干扰程度的增强，三裂叶豚草的重要值升高，同时样方中物种的丰富度随三裂叶豚草重要值的增大而下降，说明在不同生境中，三裂叶豚草的大量滋生降低了生物多样性。三裂叶豚草对入侵地生物多样性具有破坏作用，故在防除三裂叶豚草时，首先应严把植物检疫关，同时应加强生态安全宣传和生态学教育，以建立生态安全的人类生存环境。 This paper is to understand the growth of Ambrosia trifida community and to find out impact of Ambrosia trifida invasion on biodiversity. This study uses sampling method to investigate Ambrosia trifida growth habitat types and distribution of weeds around Dongling park (Dongling park has 5 points, farmlang 3 points, around high way 4 points, orchard 4 points, roadside 4 points) in Shenyang from May 28th, 2008 to June 28th, 2008. The results show that habitat distribution of the survey sample have a total of 71 kinds of weeds in 28 subjects, of which Asteraceae, Chenopodiaceae, Poly